LEARNING THE SELVO E-MODULE TO STIMULATE CRITICAL THINKING SKILLS STUDENTS - Siti Aisyah; Ratna Sari Siti Aisyah; Imas Eva Wijayanti (JCER (Journal of Chemistry Education Research), 2019)
Critical thinking skills are needed in chemistry learning, because some chemistry is contextual and in Indonesia is still relatively low. This study aims to stimulate students critical thinking skills on the topic of voltaic cells by developing the Selvo E-module apparatus. Research and development is carried out by adapting and modifying the development model through the preliminary study phase and development with limited trials. The sample in this study were students of class XI MIPA Academic Year 2018/2019. The instruments used were valid and reliable essay test questions and questionnaire sheets. Based on the findings obtained, it can be seen that the application of the Selvo E-module can stimulate students to think critically. It is seen from the average value of students pretest at 20.14 and the average posttest value of students is 85.07.